The Temperature-sensitivity of a Critical Electric Field Induced Magnetic Easy-axis Reorientation Ferromagnetic/ferroelectric Layered Heterostructures - Hong, Nguyen Thi Minh; Thang, Pham Duc; Long, Dang Dinh; Ha, Pham Thai; Trung, Nguyen Ngoc; Cong, Pham Hong; Duc, Nguyen Dinh (Communications in Physics, 2014)
We have investigated the effects of temperature on the magnetic easy axis reorientation (EARs) in polycrystalline ferromagnetic (FM) nano-scale thin films, i.e. (001)-oriented cubic films such as Fe, Ni, CFO and (0001)-oriented hexagonal films such as Co, grown on ferroelectric (FE) substrates, for example PZT, BTO substrates. The model of FM/FE bilayered heterostructures has been applied to study the total free energy of the FM films. By minimizing this energy, we have shown that temperature has a significant effect on a critical electric field induced magnetic reorientation.